Nitrogen availability in an apple orchard with weed management Disponibilidade de nitrogênio em solo de pomares de macieira com manejo de plantas espontâneas - Brunetto G. (2018)
© 2018, Universidade Federal de Santa Maria. All rights reserved.Weed management in apple orchards (Malus domestica) can affect the leaching of nitrogen (N) in soil. The study aimed to evaluate the potential leaching of N forms in soil of an apple orchard with different weed management treatments. The experiment was conducted in an apple orchard implanted in 2008. In October 2011, 80 plants were selected and the following treatments were implemented: no weed management (NM), desiccation of weeds on the tree row with herbicide use (DR) and mechanical mowing of weeds on the tree row (MR). Yield was evaluated in the 2011/2012, 2012/2013 and 2013/2014 crop seasons. In May 2012 porous cup lysimeters were installed in the NM, DR and MR treatments. In the solution collected at 0.20m, NH4+-N and NO3--N were analyzed sixteen times and mineral N concentration was calculated. The highest concentrations of NO3--N and mineral N occurred in soil solution with DR, which increases availability of the nutrient to apple trees, but also enhances the potential losses. Weed management and N flow in the solution did not affect apple yield.